2003
DOI: 10.1152/ajpheart.00714.2002
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle blood flow and flow heterogeneity during dynamic and isometric exercise in humans

Abstract: The effects of dynamic and intermittent isometric knee extension exercises on skeletal muscle blood flow and flow heterogeneity were studied in seven healthy endurance-trained men. Regional muscle blood flow was measured using positron emission tomography (PET) and an [(15)O]H(2)O tracer, and electromyographic (EMG) activity was recorded in the quadriceps femoris (QF) muscle during submaximal intermittent isometric and dynamic exercises. QF blood flow was 61% (P = 0.002) higher during dynamic exercise. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 34 publications
4
80
0
2
Order By: Relevance
“…Pincivero et al (2006) showed similar EMG amplitudes between the VL, VM and rectus femoris muscles during the concentric phase of KE contractions (similar to the contraction phase of the present KE), suggesting a similar activation of each muscle. In addition, Laaksonen et al (2003) observed no difference in blood flow between the VL and VM during dynamic KE exercise. Thus, it appears that the mosaic pattern and heterogeneity of human muscles with respect to fiber type makeup and the similar activation patterns of the VL and VM during KE may serve to attenuate any perfusion to metabolism mismatching that may occur in this model.…”
Section: Discussionmentioning
confidence: 80%
“…Pincivero et al (2006) showed similar EMG amplitudes between the VL, VM and rectus femoris muscles during the concentric phase of KE contractions (similar to the contraction phase of the present KE), suggesting a similar activation of each muscle. In addition, Laaksonen et al (2003) observed no difference in blood flow between the VL and VM during dynamic KE exercise. Thus, it appears that the mosaic pattern and heterogeneity of human muscles with respect to fiber type makeup and the similar activation patterns of the VL and VM during KE may serve to attenuate any perfusion to metabolism mismatching that may occur in this model.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the similarity of NIRS-derived oxygen saturation at 60 and 100% MVC during exercise (Fig. 5) and the comparable postexercise hyperemic response of MBF and TOI may (see below for a conflicting perspective) support the suggestion (31) that IMP at 60% MVC is sufficient to occlude blood flow to the contracting muscle, most likely at the lower-order arterioles or the capillary bed (15,28).…”
Section: Discussionmentioning
confidence: 84%
“…This increase was observed in both groups and for both veins. Dynamic exercise causes higher and less heterogeneous blood flow than intermittent isometric exercise at the same exercise intensity (Laaksonen, Kalliokoski et al, 2002). During exercise the contraction rhythm of peripheral skeletal muscles results in the compression of intramuscular veins, granting the venous blood a considerable amount of kinetic energy that facilitates its return to the heart (Stewart, Medow, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%